2016
DOI: 10.4314/tjpr.v15i6.21
|View full text |Cite
|
Sign up to set email alerts
|

Determination of acrylamide levels in selected commercial and traditional foods in Syria

Abstract: Purpose: To determine acrylamide (AA) levels in different brands of commercial and traditional foodstuffs available in Syria by ultra-performance liquid chromatography-mass spectrometery (UPLC-MS). Methods), ) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
2
5
1
Order By: Relevance
“…Our data are close to the mean and median values measured in a Swedish study of dietary intake of acrylamide for the category cookies/biscuits/wafers (300 and 230 µg kg −1 , respectively, n = 11) 13 and to the prospective sampling carried out in Italian biscuits (298 and 200 µg kg −1 , respectively, n = 44). 14 They are also in the same order of magnitude as those reported by Matthys et al 15 for conventional Belgium biscuits (range 20-1514 µg kg −1 , n = 6) and, more recently, by Alyousef et al 16 for Syrian corn and wheat-based biscuits (range 57-1433 µg kg −1 , n = 87). However, they are lower than the mean value of 495 µg kg −1 (n = 27) determined by Cengiz and Gündüz 17 during the evaluation of acrylamide exposure among Turkish toddlers from selected cereal-based products.…”
Section: Acrylamide Levels In Biscuits: the Effect Of Type Of Cereal supporting
confidence: 62%
“…Our data are close to the mean and median values measured in a Swedish study of dietary intake of acrylamide for the category cookies/biscuits/wafers (300 and 230 µg kg −1 , respectively, n = 11) 13 and to the prospective sampling carried out in Italian biscuits (298 and 200 µg kg −1 , respectively, n = 44). 14 They are also in the same order of magnitude as those reported by Matthys et al 15 for conventional Belgium biscuits (range 20-1514 µg kg −1 , n = 6) and, more recently, by Alyousef et al 16 for Syrian corn and wheat-based biscuits (range 57-1433 µg kg −1 , n = 87). However, they are lower than the mean value of 495 µg kg −1 (n = 27) determined by Cengiz and Gündüz 17 during the evaluation of acrylamide exposure among Turkish toddlers from selected cereal-based products.…”
Section: Acrylamide Levels In Biscuits: the Effect Of Type Of Cereal supporting
confidence: 62%
“…Normandi et al analyzed the acrylamide concentration in Canadian bread and found a maximum value of 107 ng/g. Also, in bread from Syria and Iran, similar results were achieved, 119 -263 µg/kg and 166 -290 µg/kg, respectively [33] [34]. These levels are identical to the results observed in the bakeries 3,13,34,36,39,40,41,42,43,44,45,46,47,48,49,50,52 and 53.…”
Section: Resultssupporting
confidence: 82%
“…In a higher range, Pacetti et al obtained an acrylamide content between 102 -594 µg/kg, which is higher than more than half of the bread samples (producers 1,3,8,10,13,19,22,23,33,34,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50, 52 and 53) [35]. Moreover, Gündüz et al analyzed bread types from Turkey and obtained a maximum of 695 µg/kg for all bread types.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the average of acrylamide in cereal products sold in the Hong Kong market was reported as 491 μg/kg [24] which is still 1.4-to 2.2-folds higher than the averages reported in this study. On the other hand, the average level of acrylamide among cereal products sold in the Syrian stands at 121 μg/kg; a value which is 1.8-to 2.9-folds lower than those reported in this study [25].…”
Section: Acrylamide Analysiscontrasting
confidence: 93%